Les adjectifs prédicatifs et les verbes qualitatifs en maninka de Guinée - Valentin Vydrin (Mandenkan)
Guinean Maninka employs two constructions meant to express property concepts: a verbal construction, with specialized construction markers (similar constructions exist in most Manding languages), and a construction with predicative adjectives (not attested in the other languages of the group). The augmenatative quality construction, a subtype of the verbal type, involves the addition of the suffix -bá to the quality verb, and the construction manifests some features of deverbalization.The inventory of the quality verbs in Guinean Maninka is reduced, they are twice as few as in Bambara. A complementary distribution is observed between quality verbs and predicative adjectives. Concepts within the semantic fields of “Dimension”, “Physical properties”, “Age”, and “Speed” are predominantly expressed by quality verbs, while “Color” and “Human propensities” are almost exclusively associated with predicative adjectivs. The concepts of the zone “Evaluation” are shared between the two classes.